PENGARUH UMUR PERUSAHAAN, PROFITABILITAS, UKURAN PERUSAHAAN, SOLVABILITAS, TERHADAP AUDIT DELAY - Farid Fadillah; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
A corporation's attested financial statement functions as a referential instrument for optimizing corporate performance, a condition which stimulates the interest of foreign investors to allocate capital to the firm. Superior-quality financial audit reports instill a high degree of confidence in their respective users. The primary objective of this empirical investigation is to ascertain the influence of company age, profitability, company size, and solvency upon the phenomenon of audit delay. The research population comprises non-cyclical consumer firms operating within the food & beverage sub-sector, as listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Sample selection was conducted employing a purposive sampling methodology based on pre-defined criteria, culminating in a final sample of 64 corporate entities. This investigation utilizes multiple linear regression analysis, facilitated by the SPSS Version 23 statistical software package. The empirical findings reveal that company age demonstrates no significant influence on audit delay. Conversely, profitability, operationalized as return on assets, and company size, quantified by firm size, both exert a statistically significant negative influence on audit delay. In contrast, solvency, proxied by the debt-to-asset ratio, exhibits a statistically significant positive influence on the same dependent variable.